2023
DOI: 10.1155/2023/1992415
|View full text |Cite
|
Sign up to set email alerts
|

Aeroengine Blade Surface Defect Detection System Based on Improved Faster RCNN

Liu Yixuan,
Wu Dongbo,
Liang Jiawei
et al.

Abstract: Aiming at the difficulty of automatic blade detection and the discontinuous defects on the full image, an aeroengine blade surface defect detection system based on improved faster RCNN is designed. Firstly, a dataset of blade surface defects is constructed. To solve the problem that the original faster RCNN is hard to detect tiny defects, RoI align is adopted to replace RoI pooling in the improved faster RCNN and the feature pyramid networks (FPN) combined with ResNet-50 are introduced for feature extraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Meanwhile, Liu et al utilized the Faster R-CNN ResNet50 neural network model to detect a range of defects present on aero-engine blades, including cracks, wrinkles, pockmarks, scratches, polishing traces, localized chromatic aberrations, and coating detachments. They also confirmed that the model achieved remarkable recognition accuracy [7]. The R-CNN family of algorithms offers significant advantages in terms of detecting accuracy; however, its limitation lies in the relatively slower detection speed.…”
Section: Introductionmentioning
confidence: 53%
“…Meanwhile, Liu et al utilized the Faster R-CNN ResNet50 neural network model to detect a range of defects present on aero-engine blades, including cracks, wrinkles, pockmarks, scratches, polishing traces, localized chromatic aberrations, and coating detachments. They also confirmed that the model achieved remarkable recognition accuracy [7]. The R-CNN family of algorithms offers significant advantages in terms of detecting accuracy; however, its limitation lies in the relatively slower detection speed.…”
Section: Introductionmentioning
confidence: 53%
“…Several studies have delved into the application of deep learning for failure detection across various manufacturing settings, particularly focusing on the outer layers of additive manufacturing (AM) parts, including turbine and compressor blades for jet engines [10][11][12]. However, the majority of these investigations have predominantly utilized traditional convolutional neural networks (CNNs), which are not optimal for spotting subtle and asymmetrical flaws.…”
Section: Introductionmentioning
confidence: 99%